Models in geomorphology- Quaternary evolution of the actual relief pattern of coastal central and northern Namib desert - Rust, U. (Bernard Price Institute for Palaeontological Research, 1980)
Field and laboratory results gained at various SWA/Namibian sites between the Kuiseb river in the south and the Unjab river in the north are presented. At the Namib coast under study two low stands of sea level and two high stands, one of them of Intra-Wurmian age, can be proved. From Toscanini northward a third (? Holocene) high stand exists besides the other two. The former shore lines can be linked spatially and temporally to the terrestrial relief sequences by means of fluvial and eolian land forms and sediments. Thus the changing patterns of more arid or more humid environments at different morphoclimatic stages up to the present one can be described. Furthermore, it is evident that the geomorphic processes themselves change regionally, and it is seen that the Central Namib desert is a geomorphologically unique area in comparison with the Skeleton Coast and the southern dune area. Finally, the tendencies of Quaternary landscape evolution even enable us to deduce some geoecological consequences concerning man's activities in this desert.
Main article
Keywords: Geomorphology; Quaternary; Namib; Desert